Perceived social support and the psychological well-being of adolescent Syrian refugees - Çakmak, Betül Gülcan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
The present study investigated the level of perceived social support (SS) and psychological well-being (well-being) in Syrian adolescents in comparison with Turkish adolescents from various socioeconomic status (SES). Also, the roles of the family SES, gender, health, and traumatic experiences on the adolescents’ well-being were investigated. Participants were 178 Syrian and 238 Turkish adolescents and their mothers. The Child and Adolescent Social Support Scale, the Strengths and Difficulties Questionnaire and a survey including questions related to the demographic and family SES information were administered to adolescents and a survey assessing the family SES, adolescents’ health and traumatic experience were administered to mothers. Based on the findings, Syrian adolescents had lower levels of SS and well-being than Turkish adolescents did. A higher level of well-being was associated with a higher level of SS (mother, teacher, and classmate). However, the correlation between SS (mother and father) and well-being varied across groups. While the relationship between teacher support and psychological difficulties was moderated by gender in both groups, the relationship between mother support and psychological difficulties was moderated by gender only in Syrian adolescents. The relationship between psychological difficulties and father support was moderated by health only in Syrian adolescents who had health-related problems. Lastly, Syrian adolescents differed on SS and well-being based on their experience of residing in refugee camps. The practical implications for school counselors were discussed.
Keywords: Refugees, Syrian -- Turkey.; Adolescent psychology.; Well-being -- Cross-cultural studies.